Nuclear pore complex components in the Malaria parasite plasmodium berghei - Kehrer, Jessica; Mair, Gunnar R.; Frischknecht, Friedrich (Scientific reports, 2018)
The nuclear pore complex (NPC) is a large macromolecular assembly of around 30 different proteins, so-called nucleoporins (Nups). Embedded in the nuclear envelope the NPC mediates bi-directional exchange between the cytoplasm and the nucleus and plays a role in transcriptional regulation that is poorly understood. NPCs display modular arrangements with an overall structure that is generally conserved among many eukaryotic phyla. However, Nups of yeast or human origin show little primary sequence conservation with those from early-branching protozoans leaving those of the malaria parasite unrecognized. Here we have combined bioinformatic and genetic methods to identify and spatially characterize Nup components in the rodent infecting parasite Plasmodium berghei and identified orthologs from the human malaria parasite P. falciparum, as well as the related apicomplexan parasite Toxoplasma gondii. For the first time we show the localization of selected Nups throughout the P. berghei life cycle. Largely restricted to apicomplexans we identify an extended C-terminal poly-proline extension in SEC13 that is essential for parasite survival and provide high-resolution images of Plasmodium NPCs obtained by cryo electron tomography. Our data provide the basis for full characterization of NPCs in malaria parasites, early branching unicellular eukaryotes with significant impact on human health.